A multi-proxy palaeoceanographic investigation of slope deposits on Porcupine Bank, NE Atlantic Ocean - Owen, Nicholas Liam (Trinity College (Dublin, Ireland). Department of Geology, 2010)
High resolution imaging of the continental slope west of the Porcupine Bank by the Irish National Seabed Survey reveals an area that is smooth and relatively undisturbed. The area lacks evidence of debris flows and canyon complexes that are prevalent on most other slope sections of the Rockall Trough, presenting a unique opportunity to examine cores along a depth transect without the issue of major down slope redistribution of sediments. Previous examinations of cores from the study area have revealed an absence of sedimentological evidence for significant gravity related remobilization and suggested that a record of bottom current activity interacting with the sea-floor is preserved.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin